IMPLEMENTASI PARADIGMA PEDAGOGI REFLEKTIF DALAM PEMBELAJARAN MATEMATIKA UNTUK MENINGKATKAN COMPETENCE, CONSCIENCE, DAN COMPASSION MAHASISWA - Haniek Sri Pratini (Elementary School: Jurnal Pendidikan dan Pembelajaran ke-SD-an, 2016)
The research was the qualitative descriptive research. The purpose of this research was to described the implementation results of the Paradigm of Reflective Pedagogy (PPR) in learning of Matematika 2 on competence, conscience, and compassion aspects. The subject of the research were 46 student participants of Matematika 2 courses of Primary School Teacher Education of Sanata Dharma University (USD). The data were collected through 1) test to measure the competence aspect and 2) questionary to measure the conscience and compassion aspects. The result showed that there was increase competence aspect, that is from 80,43% to 97,83%. There was increase in average scores on attitudes: tough, persevering, courageous, responsible, honest, independent, disciplined, open, and the value of life, that is from 3,77 (scale 1-5) to 4,07. There was increase in average scores on attitudes: cooperation, engaging, sharing, and caring, that is from 3,98 to 4,09. Implication from the result was implementation of PPR can develop students holistically, both from the aspect of competence, conscience, and compassion.